Magnitude of cesarean-section and associated factors among diabetic mothers in Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia: A cross-sectional study - Eshetu, Bajrond; Balis, Bikila; Daba, Woreknesh; Mekonnen, Bazie; Getachew, Tamirat; Roga, Ephrem Yohanes; Habte, Sisay; Bekele, Habtamu; Ketema, Indeshaw; Debella, Adera (Frontiers in Public Health, 2022)
Background: Diabetes mellitus increasingly complicates mother and fetus during perinatal period; obstructed labor, shoulder dystocia, birth injuries and increased rate of cesarean-section. As a result caesarean-section delivery continues to rise globally, it accounts more than 1 in 5 (21%) of all childbirths and 29.55% in Ethiopia despite the WHO recommendation that is the CS rate should lie between 5-15%. Methods: A facility-based cross-sectional study was conducted in Tikur Anbessa specialized hospital from February 1 to April 30 among 362 diabetic mothers. All required data were extracted from diabetic mothers chart using checklists by convenient sampling method, and incomplete records were excluded. The collected data were entered into Epi data version 4.2 and exported to SPSS version 23 for analysis. Multiple logistic regression models was fitted to identify factors associated with CS. Adjusted odds ratios along with 95% CI were estimated to measure the strength of the association and declared statistical significance at a p-value < 0.05. Results: The magnitude of cesarean-section was 57.8% (95% CI: 48.4%, 62.8%). Gestational diabetes [AOR: 2.83, (95% CI: (1.93, 8.35)], PIH [AOR: 3.35, (95% CI: (1.22, 9.20)], history of C/S [AOR: 1.62, (95% CI: (2.54, 4.83)], and fetal distress [AOR: 4.36, (95% CI: 1.30, 14.62)] were factors significantly associated with cesarean section. Conclusion: In this study, magnitude of cesarean-section was relatively high. Mothers with gestational diabetes, PIH, history of CS, and fetal distress were factors significantly associated with cesarean-section.